Multilayer Maraging/CoCrNi Composites With Synergistic Strengthening-Toughening Behavior - Chen, C. X.; Ge, Y. F.; Fang, W.; Zhang, X.; Liu, B. X.; Feng, J. H.; Yin, F. X. (Frontiers in Materials, 2021)
A novel multilayer maraging/CoCrNi composite with high mechanical properties was successfully fabricated by vacuum hot rolling and ageing treatment. The yield strength, tensile strength, uniform elongation, and fracture elongation can reach 1151MPa, 1380MPa, 15.7%, and 24% respectively, which can realize the synergistic strengthening-toughening aim by effectively improving the yield strength of CoCrNi alloy and strain hardening capacity of maraging steel. Vacuum state, high rolling reduction ratio, and alloy element diffusion are beneficial to strengthening the clad interface. The high work hardening capacity of CoCrNi alloy compensates for the severe strain softening behavior of maraging steel, effectively delaying the premature localized necking of the multilayer composites. The strengthening-toughening mechanism of the multilayer maraging/CoCrNi composites is mainly attributed to the strong interface, nanoscale precipitation and strain-induced twinning.